Integrasi Supervisi Akademik dalam Kepemimpinan Pendidikan untuk Meningkatkan Kinerja Gurudi Era Pembelajaran Abad-21 - Nani Tursina; Rudiansyah Rudiansyah (Departement of Mathematics Education, 2024)
In the current era of 21st century learning, there are many changes in the context of educational innovation determined by the government. The principal as (educational leadership) has the responsibility to design plans aimed at strengthening the implementation of the four teacher competencies, namely pedagogical, personal, social and professional competencies. Because there is a tendency for teacher performance to decline in the face of contextual and curricular changes. The integration of academic supervision becomes relevant as a strategy to support this performance improvement through providing constructive feedback and focused professional development. This research uses a qualitative research method with a descriptive analytical approach, with data collection methods analyzing scientific literature sources that are relevant to the research study. The results of this research show that the principal as an educational leader is someone who plays a big role in improving teacher performance, one of which is academic supervision, which can be a solution for developing teacher performance in the 21st century learning era. Teacher performance in the 21st century learning era requires adjustments to the development of their performance as educational staff. The role of the principal through academic supervision is that it is important to carry out his educational leadership role proactively through academic supervision, the principal can be an agent of change that ensures quality teacher performance in the 21st century learning era. Through the integration of various academic supervision approaches, both individual and group, and careful attention to aspects of planning, implementation and evaluation, school principals can create a learning environment that supports and encourages teacher professional growth. Thus, academic supervision becomes an effective tool for improving teacher performance in the 21st century learning era. Then, effective academic supervision allows teachers to continue to adapt to developments, maintain the relevance of education, and have a positive impact on student learning in the 21st century era.